Development of Information Management Skills in Teaching-Learning Processes with ICT (Docentes 2.0 Journal, 2025)
In today's digital age, information literacy (IL) has become essential for academic and professional success. This environment is characterized by a vast amount of data and a wide variety of digital sources, requiring students to acquire skills in searching for, evaluating, organizing, and using information effectively. The objective of this study was to adapt the phases of the Gavilán Model into a methodology focused on strengthening IL, thereby improving students' cognitive skills in comprehension, meaningful retention, and conceptual synthesis. The research was framed within the hermeneutic paradigm, with a qualitative approach, an interpretive method, and a narrative design of a literary and cross-sectional nature. The population consisted of students from primary school (5th grade), secondary school (10th and 11th grades), and higher education institutions (first-semester students in the Software Development Technology program), all recognized by the Colombian Ministry of National Education (MEN). In addition, academic and pedagogical documents published between 2018 and 2024 were reviewed. As a result, a technological tool was designed, organized around the four phases of the Gavilán Model, which guides students in constructing key concepts through activities that include searching for, analyzing, and synthesizing information. The proposal proved effective in promoting critical thinking, decision-making, autonomous learning, and the responsible use of information in different educational contexts.
Keywords: Information literacy; digital literacy; educational processes; ICT; meaningful learning